Determination of Electrocochleography Reference Values. Centro Médico Naval, 1993 - 1995 - Padilla La Rosa, Elsa (1999)
OBJECTIVE: To determine latency times for electrocochleographic waves in normal subjects. METHODS: During a 23-months period, 98 subjects from the Service of Otorhinolaringology at the Centro Médico Naval, Callao - Perú, underwent a single healthy ear electrocochleographic test of each individual. RESULTS: Mean latency times were similar to those redorded in other series. Among patients with 15 years-old or lesser (6,1%), latency times were longer than the average. There were no significant differences among latency times regarding to the ear side or gender. CONCLUSIONS: Electrocochleographic latency values were related to myelinization level or neurologic development of the auditive pathways.